Under a vampire moon ebook - Sands, Lynsay (Argeneau, 2012)
"Lynsay Sands writes books that keep readers coming back for more." —Katie MacAlister, USA Today bestselling author of Sex, Lies, and Vampires Lynsay Sands, the nationally bestselling author of the Argeneau/Rogue Hunter vampire series, is one of the superstars of paranormal romance. Her latest Argeneau novel, Under a Vampire Moon, features a recently single, romantically-wary mortal who encounters a gorgeous vampire male waiting for her on a pristine Caribbean beach. Under a Vampire Moon is a treat for fans of Charlaine Harris and her Sookie Stackhouse novels—for anyone, in fact, who appreciates a good island romance between a hot blooded human and a love-hungry immortal.